FDTD modeling of metamaterials [ theory and applications - Hao, Yang; Mittra, Raj (Artech House, 2009)
Artificial metamaterials have made a huge splash in antenna, microwave, and optics engineering thanks to their electromagnetic properties. And, modeling their unique characteristics and behaviors in